The Urgency of a Maintenance Statement Deed Made Before a Notary for Children Born Out of Wedlock as a Form of Ta'zir Against the Biological Father Based on Notarial Practice in Indonesia - Sari, Melia Putri Purnama (Jurnal Hukum dan Kenotariatan, 2024)
The status of children born out of wedlock carries significant consequences, especially for those who are not recognized. Recognition, which is sought through a petition in the District Court, is essential as it constitutes a form of legal protection. This effort affects the process of determining heirs and the provision of maintenance, particularly from the biological father. To ensure legal certainty, a maintenance statement deed is made before a notary as evidence for the future. This research uses a normative juridical method, employing data collection techniques from literature studies by analyzing core issues and sources from relevant legal products.